2015
DOI: 10.1002/pbc.25616
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy‐related arterial intima thickening and plaque formation in childhood cancer survivors detected with very‐high resolution ultrasound during young adulthood

Abstract: Long-term childhood cancer survivors treated with TBI during early childhood display significant signs of premature arterial aging during young adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
58
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 41 publications
7
58
3
Order By: Relevance
“…This is in agreement with two recent studies 16,17 Vatanen et al found increased carotid artery stiffness in the cohort of 19 high-risk neuroblastoma patients compared with the control group, no differences in stiffness parameters were observed when comparing total body RT with non-total body RT survivors, but the number of patients in the two groups was small. 17 Krystal et al evaluated carotid-femoral PWV in a cohort of 68 LTSCC, including non-irradiated patients, and healthy controls. LTSCC >18 years old at evaluation had significantly higher PWV compared to controls >18 years old and 70% of LTSCC >18 years had elevated PWV compared to established norms.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…This is in agreement with two recent studies 16,17 Vatanen et al found increased carotid artery stiffness in the cohort of 19 high-risk neuroblastoma patients compared with the control group, no differences in stiffness parameters were observed when comparing total body RT with non-total body RT survivors, but the number of patients in the two groups was small. 17 Krystal et al evaluated carotid-femoral PWV in a cohort of 68 LTSCC, including non-irradiated patients, and healthy controls. LTSCC >18 years old at evaluation had significantly higher PWV compared to controls >18 years old and 70% of LTSCC >18 years had elevated PWV compared to established norms.…”
Section: Discussionsupporting
confidence: 81%
“…Many authors reported on higher incidence of atherosclerotic changes in patients treated with neck RT for head and neck cancers or HD in adulthood [7][8][9][10][11][12]24,25 , and in LTSCC who were treated with RT as well. [13][14][15]17 But to our knowledge this study is the first population based study of long-term survivors of HD after neck RT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations